PS7:134 Rituximab-mediated late-onset neutropenia in systemic lupus erythematosus – distinct roles of baff and april. (21st March 2018) - Parodis, I; Söder, F; Faustini, F; Kasza, Z; Wermeling, F; Gunnarsson, I
Abstract : Background: Rituximab-mediated late-onset neutropenia (LON) has been described in various diseases. We investigated its prevalence and contributing factors, including B cell related cytokines and growth factors of the myeloid lineage, in patients with systemic lupus erythematosus (SLE). Methods: Rituximab-treated patients from the Karolinska University Hospital (n=107) were enrolled. LON was defined as an absolute neutrophil count <1, 500 cells/µL, occurring four weeks to two years following treatment, or later in cases of sustained B cell depletion, provided that other apparent causes were excluded. B cell activating factor (BAFF), a proliferation-inducing ligand (APRIL), IL-6, granulocyte-macrophage colony-stimulating factor (GM-CSF), and granulocyte colony-stimulating factor (G-CSF) were measured using ELISA prior to and post-treatment. Results: Thirty-two patients (29.9%) developed LON after a median time of 201.5 days (IQR: 66.8–322.0). Thirteen patients were admitted to the hospital; ten developed fever, and three developed critical conditions. BAFF levels increased from baseline (median: 0.62 ng/mL; IQR: 0.42–1.07) through the post-treatment measurement, both in patients who developed LON (median: 1.73 ng/mL; IQR: 1.03–2.56; p=0.005) and patients who did not (median: 1.03; IQR: 0.65–1.55; p=0.001), with significantly higher BAFF levels in the LON group (p=0.021). APRIL levels were higher in the LON group both at baseline (median: 1.54 versus 1.15 ng/mL; p=0.027) and post-treatment (median: 2.39 versus 1.11 ng/mL; p=0.011). IL-6 and GM-CSF levels decreased in the non-LON group (p<0.001). Cumulative rituximab and cyclophosphamide doses were found to be associated with the development of agranulocytosis (p=0.022 and p=0.021, respectively). Conclusion: Post-rituximab LON is a common complication in SLE. Although the phenomenon was self-limiting in most cases, a few patients developed life-threatening conditions; this highlights the importance of regular surveillance for neutrophil counts, fever and infections. Distinct roles of BAFF and APRIL are implicated; BAFF might contribute to granulopoiesis disruptions, whereas APRIL might have a value in distinguishing predisposed patients.